Perhitungan Waris - Ade Kurniawan; Yuyun Sapitri (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This article discusses the importance of inheritance law in Indonesia in the social and economic life of society. Through a comprehensive analysis, this article describes the basic concepts of heirs, inheritance, inheritance debt, and inheritance calculations in the context of inheritance law in Indonesia. The research method used is literature study, where data is obtained from relevant scientific literature. Data analysis is carried out by summarizing information from various sources to develop a comprehensive understanding. This article does not use primary data, but instead relies on secondary data from previously published literature. The problem of the complexity of various inheritance law systems is the main focus, which requires in-depth understanding by the public. The discussion in this article provides a better understanding of the rights and obligations as heirs as well as the process of dividing inheritance assets fairly in accordance with the provisions applicable in Indonesia. Thus, this article makes an important contribution in increasing public awareness about the importance of a comprehensive understanding of inheritance law in this country.